Peminggiran Perempuan dalam Pernikahan (Kasus Nikah Sirri dan Nikah Usia Dini) - Muhammad Gazali Rahman (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
Sirri clearly has no legal power, each husband and wife do not have Deed of Marriage, the government in this case Office of Religious Affairs (for the Muslims) do not give them Quotation Deed of Marriage as a handle and evidence has been conducted legitimate marriage. Negative impact for woman (wife) if in the journey of fostering household happening disharmony, disputes, quarrel until happened domestic violence (KDRT), a wife feel tortured and depressed live with her husband, whereas during marriage husband and wife already have joint property Controlled by her husband, a woman as a wife would not be able to claim her rights by filing a lawsuit in the Religious Courts for not having legitimate proof of her marriage. Similarly, with an early age marriage, which is one partner, both men and women are not old enough or under age, then the marriage that looked